Taxonomy and ultrastructure of phytal harpacticoid copepods from Malay Peninsula - Nurul Huda Ahmad Ishak (Fakulti Sains dan Teknologi, 2011)
Aquatic vegetation is the main breeding area for marine life, and harpacticoida are often dominant taxon in marine algae. They arc associated with sessile epibenthic macrofauna and microphytes, where they can make up a large of the phytal meiofauna. Thus, a study on taxonomy and ultrastructure of phytal harpacticoid copepods was conducted in Malay Peninsula. The objectives of this research were to do a taxonomic identification of the dominant species of harpacticoid copepods associated with seaweed and seagrass in Malay Peninsula; and to determine the ultrastructure of phytal harpacticoids using Scanning Electron Microscope (SEM).